Inequality by design : cracking the bell curve myth - Fischer, Claude S., 1948- (Princeton University Press, 1996)
As debate rages over the widening and destructive gap between the rich and the rest of Americans, Claude Fischer and his colleagues present a comprehensive new treatment of inequality in America. They challenge arguments that expanding inequality is the natural, perhaps necessary, accompaniment of economic growth. They refute the claims of the incendiary bestseller The Bell Curve (1994) through a clear, rigorous re-analysis of the very data its authors, Richard Herrnstein and Charles Murray, used to contend that inherited differences in intelligence explain inequality. Inequality by Design offers a powerful alternative explanation, stressing that economic fortune depends more on social circumstances than on IQ, which is itself a product of society. More critical yet, patterns of inequality must be explained by looking beyond the attributes of individuals to the structure of society. Social policies set the "rules of the game" within which individual abilities and efforts matter